"Sarvada Sarvabhavanam Samanyam Vriddhikaranam’’ for the Corroboration of the Theory, the Medical Study of Shukrajanan Mahakashaya and Shukrashodhan Mahakashaya in Ksheenashukra (Oligospermia) - Saini, Dholaram; Dhiman, Baldev Kumar (International Research Journal of Ayurveda & Yoga, 2022)
Man in the modern era is fastened by many physical and mental ailments. Ksheenashukra is one of the diseases caused by vitiated Vata and Pitta. The present study deals with sample size of 20 patients who presented with Ksheenashukra symptoms in two groups each for 2 months. Group -A were given Shukrajanan Mahakashaya and Group B were given Shukrashodhan Mahakashaya. The herbs which were not available were substituted by representative herbs. The medicines given were in form of decoction; dose 20 ml BD for two months. According to the basic principles of Ayurveda that is principle of Samanya (similar identities) the properties identical to those of Shukra Dhatu will help it to increase in the body. At the end of the trial the comparative study of both the groups was comprehended in form of results. In case of quantitative ( sperm count, PH, volume of semen) analysis Group-A showed better results. In case of qualitative analysis (motility of sperms) Group B was found better than Group-A. With respect to subjective parameters Group A Showed better results than Group- B.